Analysis of the Propulsion Performance and Internal Flow Field of an Underwater Launcher - Xinwei Zhang; Yonggang Yu (Applied Sciences, 2022)
The gas-curtain launch is designed to address the shortcomings of conventional underwater launchers, such as poor dependability and low muzzle velocity. In this paper, the influence of jet structures on the propulsion performance and internal flow field of an underwater gas-curtain launcher is investigated. To conduct the experiment on a small-aperture underwater launcher, three projectiles with different jet structures were designed. The experimental results show that a projectile with a central nozzle is more conducive to gas-curtain formation than one with four sidewall grooves. Additionally, the central nozzle can reduce launch resistance and improve propulsion performance more effectively. Furthermore, increasing the diameter of the central nozzle aids in gas-curtain formation and propulsion performance. Following the experiment, a numerical model of the internal flow field for gas-curtain launch is built in order to develop numerical simulations under three jet structures. The calculation results show that the three gas-curtain projectiles can likewise acquire good propulsion performance. Different jet structures have significant impacts on the launching resistance of a gas-curtain launcher, thereby affecting its propulsion performance. The launch resistance is lower when the central nozzle jet structure is utilized; however, the muzzle velocity is also lower because more gas is consumed for drag reduction and the projectile force area is smaller. This study reveals the effect of jet structure on the propulsion performance and flow field evolution of a gas-curtain launcher.